ANALISIS KADAR LOGAM BERAT KADMIUM (Cd) PADA AIR MINUM ISI ULANG DEPOT AIR MINUM DI KECAMATAN KOTA ANDIR KOTA BANDUNG - Aeni, Suci Rizki Nurul; Muhtar, Putri Mutiara; Ayu Nuralifah Anggraeni (Jurnal Kesehatan - STIKes Prima Nusantara, 2025)
Background: Many people use Refillable Drinking Water Depots (DAMs) as drinking water, although their quality is still questionable, especially related to their heavy metal content. Objectives: To determine the cadmium (Cd) level of refillable water at the Drinking Water Depot (DAM) in Andir District, Bandung City. Methods: The method in This study uses a descriptive method with a cross-sectional design. The cadmium (Cd) content in refillable drinking water (DAM) samples was analyzed using atomic absorption spectrophotometry (SSA).   Results: The measurement results showed that the level of cadmium (Cd) in refillable drinking water (DAM) ranged from -0.0055 to -0.0030 mg/L. Based on the data, it was known that all samples met the quality standard for the requirements for cadmium heavy metal (Cd) content in Permenkes No.2 of 2023 concerning the Quality Standard for refillable drinking water of 0.003 mg/L. Conclusion: Based on this study, of the 10 Drinking Water Depots (DAMs) studied, all of them meet the requirements for metal content in accordance with SNI 01- 3553-2006 and Government Regulation Number 2 of 2023. Therefore, the cadmium (Cd) level of refillable drinking water in Andir District, Bandung City, can be considered to meet the standards and is suitable for consumption.